Contents of O-containing functional groups in coals by 13C NMR analysis - Wang, Y.; Zhou, J.; Chen, Y.; Hu, X.; Zhang, Shu; Lin, X. (2013)
The solid state high resolution 13 C CP/MAS NMR technology was employed to analyze O-containing functional groups in 4 coals. The variation and contents of inactive O-containing functional groups in the coals were obtained in combination with chemical method. The results show that the 13 C CP/MAS NMR method is effective to obtain the contents of some O-containing functional groups. The contents of carboxyl and carbonyl in the low rank coal are from 0.00 to 1.41 and from 0.45 to 1.91 mol/kg, respectively. Combined with chemical method, the content of ether bond is obtained, which is from 5.33 to 10.54 mol/kg. However, the value of inactive ether bond in the coals is only from 0.04 to 0.13 mol/kg, and the occurrence of the ether bond is predominantly inactive, few of them exists in high rank coal.